Evolved high aerobic capacity has context-specific effects on gut microbiota - Hanhimäki, Elina; Watts, Phillip C.; Koskela, Esa; Koteja, Paweł; Mappes, Tapio; Hämäläinen, Anni M. (Frontiers in Ecology and Evolution, 2022)
Gut microbiota is expected to coevolve with the host’s physiology and may play a role in adjusting the host’s energy metabolism to suit the host’s environment. To evaluate the effects of both evolved host metabolism and environmental context in shaping the gut microbiota, we used a unique combination of 1) experimental evolution to create selection lines for fast metabolism and 2) a laboratory-to-field translocation study. Mature bank voles Myodes glareolus from lines selected for high aerobic capacity (A) and from unselected control (C) lines were released into large (0.2 ha) outdoor enclosures for longitudinal monitoring. To examine whether the natural environment elicited a similar or more pronounced impact on the gut microbiota of the next generation, we also sampled the field reared offspring. Gut microbiota were characterised using 16S rRNA amplicon sequencing of faecal samples. Artificial selection for fast metabolism had minimal impact on the gut microbiota in laboratory conditions, but in field conditions there were differences between selection lines (A vs. C) in the diversity, community, and resilience of the gut microbiota. Notably, the selection lines differed in the less abundant bacteria throughout the experiment. The lab-to-field transition resulted in an increase in alpha diversity and an altered community composition in the gut microbiota, characterized by a significant increase in the relative abundance of Actinobacteria and a decrease of Patescibacteria. Also, the selection lines showed different temporal patterns in changes in microbiota composition, as the average gut microbiota alpha diversity of the C, but not A-lines, was temporarily reduced during the initial transition to the field. In surviving young voles, the alpha diversity of gut microbiota was significantly higher in A-line than C-line voles. These results indicate that the association of host metabolism and gut microbiota is context-specific, likely mediated by behavioural or physiological modifications in response to the environment.